2000
DOI: 10.1046/j.1365-2168.2000.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of sentinel lymph node biopsy for staging melanoma

Abstract: The sentinel node status was a strong prognostic factor, even with a false-negative rate of 11 per cent. Published in abstract form as Eur J Nucl Med 1999; 26(Suppl): S57

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
75
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(87 citation statements)
references
References 17 publications
10
75
0
2
Order By: Relevance
“…The histological status of the SLN has been found to be an indicator representative of the whole LN basin. It has turned out to be the strongest prognostic factor for tumor recurrence and survival [2][3][4][5][6] , and a major decision criterion for adjuvant therapy [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…The histological status of the SLN has been found to be an indicator representative of the whole LN basin. It has turned out to be the strongest prognostic factor for tumor recurrence and survival [2][3][4][5][6] , and a major decision criterion for adjuvant therapy [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…6 Breslow thickness (measured in millimeters) is the only reproducible factor predictive of SLN status in all studies. [1][2][3][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several other factors have been variably and sometimes discordantly reported to have predictive value for SLN metastasis, including Clark level, ulceration, mitotic rate, microsatellitosis, angiolymphatic invasion, vertical growth phase, number of nodal basins, primary tumor location, and patient age. [1][2][3][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several plausible explanations could account for the disparate and sometimes conflicting predictive models that have been offered to date.…”
mentioning
confidence: 99%
“…With long-term follow-up of patients with negative sentinel nodes there is a small but definite incidence of recurrence in the mapped and sampled nodal basin. 5,[10][11][12][13][14][15][16][17][18][19] These patients may be considered to have a false-negative result of their sentinel node biopsy procedure. Previous reports have suggested that the majority of patients who recur in the relevant node field will, in fact, have identifiable metastases in the biopsied sentinel node if a more comprehensive histopathologic evaluation of the node is undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Furthermore, the presence or absence of metastases in the sentinel node is the most important prognostic factor for melanoma patients. 9 For a sentinel node to provide accurate prognostic information, it is essential that 'true' sentinel nodes are removed and examined thoroughly.…”
mentioning
confidence: 99%
See 1 more Smart Citation